Netscan and Networx for Management Bandwidth and Traffic with Simple Routing - Mufadhol Mufadhol; Guruh Aryotejo; Agus Wibowo (Universitas Ahmad Dahlan, 2017)
Currently, approximately 3.4 billion people are accessing the internet around the world and that number is still growing. This phenomena creates the Internet culture that has a great influence on science, technology and even the world economy. Internet bandwidth is very expensive, which makes an information technology based company have to map the internet accurately either daily, monthly or yearly. That data will be taken into consideration by the company to decide how to provide services that make an internet surfing is a pleasant experience. If not regulated, most likely the traffic and bandwidth will be used up even when it is only shared by a few users. To anticipate this, we need a bandwidth and management traffic system using Netscan and Networx in order to monitoring the usage of Internet.